2016
DOI: 10.1128/jcm.02577-15
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Copan WASP for Routine Urine Microbiology

Abstract: This study compared a manual workup of urine clinical samples with fully automated WASPLab processing. As a first step, two different inocula (1 and 10 l) and different streaking patterns were compared using WASP and InoqulA BT instrumentation. Significantly more single colonies were produced with the10-l inoculum than with the 1-l inoculum, and automated streaking yielded significantly more single colonies than manual streaking on whole plates (P < 0.001). In a second step, 379 clinical urine samples were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…[5][6][7][8][9] Previously, Croxatto et al 5 demonstrated that urine specimens processed with the benchtop InoqulA model resulted in better isolated colonies and fewer subcultures. This confirmed the observations made previously by Froment et al 6 with the Kiestra InoqulA and Quiblier et al 10 with urine specimens processed with the Copan WASP system. Croxatto et al 5 and Iversen et al 8 compared the performance of BD Kiestra InoqulA and Copan WASP with urine specimens and reported more isolated colonies from the InoqulA system.…”
Section: Discussionsupporting
confidence: 91%
“…[5][6][7][8][9] Previously, Croxatto et al 5 demonstrated that urine specimens processed with the benchtop InoqulA model resulted in better isolated colonies and fewer subcultures. This confirmed the observations made previously by Froment et al 6 with the Kiestra InoqulA and Quiblier et al 10 with urine specimens processed with the Copan WASP system. Croxatto et al 5 and Iversen et al 8 compared the performance of BD Kiestra InoqulA and Copan WASP with urine specimens and reported more isolated colonies from the InoqulA system.…”
Section: Discussionsupporting
confidence: 91%
“…This process can be at least partly automated but (in our experience) requires continuous monitoring and significant residual manual input from appropriately qualified and experienced laboratory technologists. Although comparison of manual and automated urine cultures showed that automation increased the number of positive samples and generated greater microbial diversity among positive samples, there was no evidence for better time to result, and the different positivity rates were not significantly different (27). Additional health economics studies describing the financial consequences of TLA are still much needed.…”
Section: Consolidation Through Laboratory Automationmentioning
confidence: 99%
“…Classical culture-based microbiology provides important subject matter as to how TLA improves processes at various levels. Automated plate and broth inoculation saves labor by eliminating repetitive and manual tasks while adding the benefit of producing more isolated bacterial colonies (27,30,31). Due to the variety of incoming specimens, a preanalytical step may be required.…”
Section: Is Total Laboratory Automation Already Practical and Mature?mentioning
confidence: 99%
“…Automation in the clinical laboratory has developed significantly over the years, beginning with automated streaking instrumentation and culminating in total laboratory automation (TLA) that inoculates, streaks, images plates, and incubates cultures. The two most prominent automation systems are the WASPLab software (Copan Diagnostics, Brescia, Italy) and the BD Kiestra system (Becton, Dickinson, Franklin Lakes, NJ), both of which have been reported to improve consistency in plating and free up the technologist's time to perform other duties (14,15). Image analysis software has been added to these systems and has demonstrated high sensitivity for detecting growth on chromogenic agar for patient screening (16)(17)(18).…”
mentioning
confidence: 99%